Ancaman Masuknya Virus Penyakit Mulut dan Kuku Melalui Daging Ilegal di Entikong, Perbatasan Darat Indonesia dan Malaysia - Risma JP Silitonga (Jurnal Sain Veteriner, 2016)
This study was aimed to analyze the risk of FMD virus to enter Indonesia by the presence of illegal meat at Entikong, a borderland between Indonesia and Malaysia. The primary datas were collected using questionnaires method to collect expertise, in-depth interviews, and direct field observations. Secondary datas were obtained from scientific publications and articles or unpublished datas (statistics, goverment documents and reports). The respondents were choosen by purposive sampling. The circulating illegal meat was possibly originate fromdifferent countries, including FMD-endemic countries/zones such as Peninsular Malaysia, Thailand, India and even unidentified countries/zones according to our respondends. The types of illegal meat such as frozen deglanded bonein-meat and frozen deglanded offal that enter Entikong carry the risk of becoming a source of FMD infection. Based on the entry route, delivery frequency, and meat volume, ilegal meat was possibly also entered into Indonesia using non-vehicular transportation. These conditions indicated that the entrance of illegal meat could pose risk of the FMD virus entry to Indonesia, especially at the borderland between Indonesia and Malaysia at Entikong. It is highly recommended to apply strict inspection at the border entraces and increase collaboration with related institutions to prevent the entrance of illegal meat and to reduce the entry risk of FMD virus.